The Cluster Concept at Los Angeles Mission College (Distributed by ERIC Clearinghouse, 1976)
This report describes the organizational plan of Los Angeles Mission College (LAMC). LAMC has chosen a structure stemming from the cluster concept, involving semi-autonomous clusters, each small in size. These characteristics enhance student-faculty-administrator relations and permit each instructional unit to participate directly in its own evolution. At the same time, some services are centrally provided, thereby reducing costs by eliminating unnecessary duplication. LAMC's clusters will contain approximately 1,000 FTE students and 30 FTE faculty, organized around instructional programs, yet as educationally comprehensive as possible. Each cluster will have its own student government, with student activities emanating from the cluster. LAMC is functionally organized in three tiers: the office of the president, the office of the dean of the college, and the clusters. Policy formulation and implementation flow through a system of councils (administrative, academic, and student) and the three-tier structure. The LAMC plan is compared in detail to those at five other cluster community colleges in California. Organization charts, curricula, administrative salaries, and other statistical comparisons for the five colleges are presented in appendices. (Author/JDS)